Human granzyme B regulatory B cells prevent effector CD4+CD25- T cell proliferation through a mechanism dependent from lymphotoxin alpha - Sailliet, Nicolas; Mai, Hoa-Le; Dupuy, Amandine; Tilly, Gaëlle; Fourgeux, Cynthia; Braud, Martin; Giral, Magali; Robert, Jean-Michel; Degauque, Nicolas; Danger, Richard; Poschmann, Jeremie; Brouard, Sophie (Frontiers in Immunology, 2023)
Introduction Human Granzyme B (GZMB) regulatory B cells (Bregs) have suppressive properties on CD4+ effector T cells by a mechanism partially dependent on GZMB. Moreover, these cells may be easily induced in vitro making them interesting for cell therapy. Methods We characterized this population of in vitro induced GZMB+Bregs using single cell transcriptomics. To investigate their regulatory properties, Bregs or total B cells were also co-cultured with T cells and scRNAseq was used to identify receptor ligand interactions and to reveal gene expression changes in the T cells. Results We find that Bregs exhibit a unique set of 149 genes differentially expressed and which are implicated in proliferation, apoptosis, metabolism, and altered antigen presentation capacity consistent with their differentiated B cells profile. Notably, Bregs induced a strong inhibition of T cell genes associated to proliferation, activation, inflammation and apoptosis compared to total B cells. We identified and validated 5 receptor/ligand interactions between Bregs and T cells. Functional analysis using specific inhibitors was used to test their suppressive properties and we identified Lymphotoxin alpha (LTA) as a new and potent Breg ligand implicated in Breg suppressive properties. Discussion We report for the first time for a role of LTA in GZMB+Bregs as an enhancer of GZMB expression, and involved in the suppressive properties of GZMB+Bregs in human. The exact mechanism of LTA/GZMB function in this specific subset of Bregs remains to be determined.